2019
DOI: 10.1002/jcsm.12375
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondrial oxidative stress impairs contractile function but paradoxically increases muscle mass via fibre branching

Abstract: Background Excess reactive oxygen species (ROS) and muscle weakness occur in parallel in multiple pathological conditions. However, the causative role of skeletal muscle mitochondrial ROS (mtROS) on neuromuscular junction (NMJ) morphology and function and muscle weakness has not been directly investigated. Methods We generated mice lacking skeletal muscle‐specific manganese‐superoxide dismutase (m Sod2 KO) to increase mtROS using a cre‐Lox app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 67 publications
(182 reference statements)
2
56
0
Order By: Relevance
“…Damaged proteins induce an increase in activation of protein breakdown signalling, promoting muscle loss. 10,11 Tissues possess scavenging antioxidant enzymes that act to neutralize radicals and prevent oxidative stress-mediated tissue dysfunction. 12 However, scavenging enzymes are dysregulated in many disease conditions, 13,14 leading to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Damaged proteins induce an increase in activation of protein breakdown signalling, promoting muscle loss. 10,11 Tissues possess scavenging antioxidant enzymes that act to neutralize radicals and prevent oxidative stress-mediated tissue dysfunction. 12 However, scavenging enzymes are dysregulated in many disease conditions, 13,14 leading to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Because this ROS potentiation in type II fibers is coupled with decreased ability to combat lipid stress in comparison to type I fibers, cellular homeostasis is disrupted predisposing the proteins and other cellular components to damage and dysfunction. In fact, compromised cellular redox homeostasis is suggested for impairments in NMJ integrity and function (Sakellariou et al 2017) (Ahn et al 2019) and likely contributes in the observed accelerated alterations in the NMJs of type II fibers with aging (Prakash and Sieck 1998).…”
mentioning
confidence: 99%
“…While muscle respiration depends on electrons entering the electron transport chain from both complexes I and II, fat mitochondria depend primarily on complex II-linked respiration. ETC complex II is highly sensitive to oxidative damage, which could partially explain the age-related decrease in OXPHOS capacity [92]. Basal hydroperoxide production was approximately 4.5 times higher in fat biopsies than in muscle.…”
Section: Discussionmentioning
confidence: 97%